Factors associated with personal protective equipment use among pesticide handlers in Mwea irrigation Scheme, Kenya - Kinyua, Fredrick G.; Odongo, Alfred O.; Nguku, Julius (International Journal Of Community Medicine And Public Health, 2023)
Background: Pesticide use among small scale rice farmers has drastically increased over time globally. Evidence shows that majority of pesticide handlers do not regard PPE use during pesticide application, hence low PPE compliance. Methods: This study explored factors associated with PPE use among pesticide handlers in Mwea Irrigation Scheme, Kenya. The study was cross-sectional involving 246 respondents. Results: There was low level of PPE use among pesticide handlers with none using full PPE and only 25.2% using 4-6 PPE items out of 7 possible items. The most used PPE were trousers (74.4%), long-sleeved shirt/jacket (65.9%) and hat (60.6%). The least worn PPE were gumboots (1.6%), gloves (2.8%) and goggles (9.8%). Chi- square tests of independence revealed that sex, age, crop ownership, pesticide safety training, pesticide application experience, pesticide safety knowledge, attitude towards PPE use, perceived environmental health risk and Perceived PPE importance were significantly associated with PPE use. However, level of education, land tenure status and size of the farm were found not to have any association with PPE use. Conclusions: The results provide insights for future interventions and inform focus areas by health and safety enforcement agencies and policy developers. More training on pesticide safety and PPE use will enhance compliance and promote pesticide handlers’ health.